Predictors of Mortality and Neurological Recovery in Patients with Intracerebral Hemorrhage - Muhammad Tahir, Madiha Amjad, Ashan Ali, Muhammad Azhar Qureshi, Muhammad Inam, Saadullah Afridi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: High mortality and long-term neurological impairment are linked to intracerebral hemorrhage (ICH), a severe type of hemorrhagic stroke. Improving patient outcomes requires early identification of mortality and recovery determinants. Objective: The goal is to identify the factors that influence patients with intracerebral hemorrhage in terms of neurological recovery and mortality. Material & Mathods: From August 2022 to August 2023, this descriptive observational study was carried out at Allied Hospital Faisalabad. There were 150 patients in all who had been diagnosed with spontaneous intracerebral hemorrhage. Clinical information was collected, including the Glasgow Coma Scale (GCS), comorbidities, and radiological findings such the location, volume, and intraventricular extension of the hematoma. The Modified Rankin Scale (mRS) was used to evaluate the results. SPSS version 26 was used to analyze the data, and p < 0.05 was deemed significant. Result: Findings: The patients were 58% male and had a mean age of 61.4 ± 13.2 years. The overall death rate was 34%. Low GCS (≤8), high hematoma volume (>60 mL), intraventricular extension, and brainstem involvement were all substantially linked to poor outcomes (p < 0.05). Patients with smaller hematoma volumes and higher GCS scores showed better neurological recovery. Conclusion: In conclusion, intraventricular extension, a big hematoma volume, and a low GCS score are all significant indicators of mortality in cases of intracerebral hemorrhage. For prompt care and better neurological outcomes, early identification of these factors is crucial. Keywords: Allied Hospital Faisalabad intracerebral hemorrhage, mortality predictors neurological recovery; Glasgow Coma Scale hematoma volume stroke outcomes.